(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the 1997 Punjab State Assembly elections through the conceptual lens of critical election theory to assess whether the electoral outcome signified a process of electoral realignment in the state’s party system. Critical elections are understood as transformative political events that generate enduring shifts in voter loyalties, party dominance, and patterns of political competition. The paper situates the 1997 elections within Punjab’s distinctive socio-political context, shaped by a decade of militancy, political instability, and the subsequent re-legitimation of democratic institutions. Using electoral data, party performance trends, and voting behaviour patterns, the study examines the extent to which the elections marked a departure from earlier alignments and contributed to a restructuring of political power in the state. It evaluates whether the decisive mandate reflected short-term voter reaction to governance failures or a deeper realignment in political preferences with long-term consequences. By analysing continuity and change across successive elections, the paper contributes to the broader debate on the applicability of critical election theory to sub-national politics in India and enhances understanding of electoral transformation in post-conflict democratic settings.